Long-term application of hydroxychloroquine could not prevent the infection of COVID-19 - Yin Zhu; Yongping Chen; Yuewen Gong; Aijun Pan; Huijie Ding; Jianjiang Fang; Biyun Yu; Boding Wang; Chunhai Ke; Lanman Xu (Journal of Infection in Developing Countries)
Introduction: Current pandemic of the coronavirus induced disease 2019 (COVID-19) presents an urgent issue to the world due to lack of vaccine and medication. Hydroxychloroquine (HCQ) has generated a lot of controversies whether it is effective in prevention and treatment of COVID-19. Current report presents a 63-year-old woman who has taken HCQ for many years but still infected by COVID-19.